Chemical Composition of Cymbopogon flexuosus and C. winterianus Essential Oils and Their Insecticidal Potential Against the Coffee Berry Borer Hypothenemus hampei - Melally Giddegowda Venkatesha; Rudramuni Kiran (Jurnal Proteksi Tanaman)
Hypothenemus hampei is the most important insect pest of coffee in the world. H. hampei is controlled by using endosulfan and methyl bromide. However, using these two chemicals may pose pesticide resistance, bioaccumulation, and a threat to human health and the environment. This study evaluated the chemical compositions of essential oils from Cymbopogon flexuosus and C. winterianus and their insecticidal potential against H. hampei as an alternative to endosulfan and methyl bromide. The chemical profiles of the two essential oils showed that both constituted biochemically distinct monoterpenes and sesquiterpenes. The main compounds identified in C. flexuosus were citral, geraniol, and isoforms, representing 76.45% of the total composition, and other active ingredients were citronella, caryophyllene, citronellyl acetate, cadinene, linalool, and limonene. The composition of C. winterianus was citronella, nerol, and citronellol as principal components, corresponding to 66.47%, along with other active ingredients elemol, geranyl acetate, citronellyl acetate, germacrene, and limonene. Differential sensitivity of H. hampei adults was observed in the bioassay of two oils, where a dose-dependent increase in mortality was observed. Among two concentrations of both essential oils, 100% mortality was observed at 500 and 1000 ppm within 48 and 24 hours of treatment, respectively. The significant biological activity of both Cymbopogon species oils indicated a potential source for further development of botanical pesticides as an effective, useful alternative for currently used toxic insecticides. Additionally, essential oils of C. flexuosus and C. winterianus and their active ingredients are classified as non-residual insecticides and are eligible for a pesticide registration exemption.